Analisis Sentimen terhadap Perpanjangan Masa Jabatan Presiden Indonesia Menggunakan Naïve Bayes - Hanif, Zuhdi; Surapati, Untung (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Twitter social media is often used as a medium to express opinions on the government in Indonesia. There  are  also  many  controversial  things  on  Twitter  social  media  against  the  government,  as  is  the case  today  there  is  a  controversy  wherethere  is  a  proposal  to  make  the  term  of  office  of  the President in Indonesia three periods, which previously could only serve up to two terms or ten years. for  one  President.  Public  opinion  or  sentiment  which  in  Twitter's  terms  is  commonly  referred  to  as "shrink"  can  be  in  the  form  of  negative  or  positive  opinions.  However,  the  amount  of  data  is  quite large  so it takes a method that can be used to make it  happen, namely by using sentiment analysis. Sentiment  analysis  can  be  used  as  a  solution  to  process  these  opinions  using  the  Naïve  Bayes Classifier  algorithm.  The  results  of  the  nave  Bayes  technique  require  evaluation  to  determine  the best model. The test is carried out with three models, namely 70:30, 80:20, and 90:10 which are then evaluated using a confusion matrix. Based on the comparison of the evaluation test results, the best scenario for the Naïve Bayes  classification model is in the first scenario or model (90% training data and 10% testing data) with an accuracy value of 95%, a precision value of 97%, a recall value of 96%, and the f-measure value is 96%.
Keywords: Sentiment Analysis; Naïve Bayes; President of Indonesia; Sentiment Score; Twitter